Pembelajaran Pias Huruf dalam Meningkatan Pemahaman Huruf Vokal dan Huruf Konsonan pada Siswa Tunaganda di SLB Bhakti Luhur Baumata Kupang - Bessie, Juandres; Wangge, Vinsensius; Selan, Ot Bil Wilson (Indo-MathEdu Intellectuals Journal, 2025)
Developing basic literacy skills in children with learning disabilities requires adaptive learning strategies based on concrete media. One of the main challenges is the students' limited ability to recognise and arrange letters systematically. This study aims to describe the process of using letter tiles, improvements in student learning outcomes, and the responses of teachers and parents to their implementation at the Bhakti Luhur Baumata Kupang Special School. The method used was classroom action research with a descriptive qualitative approach, involving one student with special needs. Data were collected through observation, tests, interviews, and documentation, then analysed through data reduction, data presentation, and conclusion drawing. The results of the study indicate that letter stencils are effective in improving the ability to recognise vowels and consonants, pronounce letters correctly, and arrange letters into simple syllables. Student learning scores improved to the good category, accompanied by positive responses from teachers and parents. These findings confirm that letter stencils are an adaptive and enjoyable learning medium that can increase student motivation and confidence